Hospital discharge information after elective total hip or knee joint replacement surgery: A clinical audit of preferences among general practitioners - Briggs, Andrew; Lee, N.; Sim, M.; Leys, T.; Yates, P. (Australasian Medical Journal Pty Ltd, 2012)
The demand for elective joint replacement (EJR) surgery for degenerative joint disease continues to rise in Australia, and relative to earlier practices, patients are discharged back to the care of their general practitioner (GP) and other community-based providers after a shorter hospital stay and potentially greater post-operative acuity. In order to coordinate safe and effective post-operative care, GPs rely on accurate, timely and clinically-informative information from hospitals when their patients are discharged. The aim of this project was to undertake an audit with GPs regarding their preferences about the components of information provided in discharge summaries for patients undergoing EJR surgery for the hip or knee. GPs in a defined catchment area were invited to respond to an online audit instrument, developed by an interdisciplinary group of clinicians with knowledge of orthopaedic surgery practices. The 15-item instrument required respondents to rank the importance of components of discharge information developed by the clinician working group, using a three-point rating scale.Fifty-three GPs and nine GP registrars responded to the audit invitation (11.0% response rate). All discharge information options were ranked as ‘essential’ by a proportion of respondents, ranging from 14.8–88.5%. Essential information requested by the respondents included early post-operative actions required by the GP, medications prescribed, post-operative complications encountered and noting of any allergies. Non-essential information related to the prosthesis used. The provision of clinical guidelines was largely rated as ‘useful’ information (47.5–56.7%). GPs require a range of clinical information to safely and effectively care for their patients after discharge from hospital for EJR surgery. Implementation of changes to processes used to create discharge summaries will require engagement and collaboration between clinical staff, hospital administrators and information technology staff, supported in parallel by education provided to junior medical staff.